Находка грегарин в некоторых акароидных клещах - Костенко, С.М.; Акимов, И.А.; Старовир, И.С. (Вестник зоологии, 1978)
Finding of Gregarinidae in the intestine of mites from the Acaridae and Glycyphagidae families are mentioned. Gregarinidae are located in the largest division of the mite intestine — ventriculus.